The Role of Islamic Education Teachers in Instilling Religious Moderation Values of High School Students - Muhammad Iqbal Kurniawan; Imam Ahmad Amin (At-Ta'lim : Media Informasi Pendidikan Islam, 2024)
ENGLISH: The Role of Islamic Education Teachers in Instilling Religious Moderation Values of High School StudentsObjective: This study aims to determine the role and strategies of Islamic Education Teachers in instilling Religious Moderation in Students at SMA IT IQRA' Bengkulu City. Method: this type of research uses qualitative-descriptive with case study design. This research was conducted in 2024; the main subjects were Islamic Education Teachers and the Head of the school curriculum. Data collection used interview, observation, and documentation instruments. Descriptive analysis was used to analyze the research data. Results: The role of Islamic Religious Education teachers at SMA IT Iqra' Bengkulu City is strategic in instilling religious moderation values in students. The values of religious moderation are integrated into the subject matter, such as explaining the concept of wasathiyah (balance), tolerance, and unity in Islamic teachings. Conclusion: Islamic Education teachers become role models for students by showing religious moderation in daily interactions in the school environment and relationships with the surrounding community. Contribution: This research contributes to the scientific literature, especially in Islamic education and the study of religious moderation.INDONESIAN: Peran Guru Pendidikan Agama Islam dalam Menanamkan Nilai-Nilai Moderasi Beragama Siswa SMATujuan: Penelitian ini bertujuan untuk mengetahui Peran dan strategi Guru Pendidikan Agama Islam dalam menanamkan Moderasi Beragama pada Siswa di SMA IT IQRA’ Kota Bengkulu. Metode: jenis penelitian menggunakan kualitatif-deskriptif dengan desain studi kasus. Penelitian ini dilaksanakan pada tahun 2024, subjek utama yaitu Guru Pendidikan Agama Islam dan Kepala kurikulum sekolah. Pengumpulan data menggunakan instrumen wawancara, observasi, dan dokumentasi. Analisis deskriptif digunakan dalam analisis data penelitian. Hasil: Peran guru Pendidikan Agama Islam di SMA IT Iqra’ Kota Bengkulu sangat strategis dalam menanamkan nilai-nilai moderasi beragama kepada siswa. Nilai-nilai moderasi beragama diintegrasikan dalam materi pelajaran, seperti penjelasan tentang konsep wasathiyah (keseimbangan), toleransi, dan persatuan dalam ajaran Islam. Kesimpulan: Guru Pendidikan Agama Islam menjadi teladan bagi para siswa dengan menunjukkan moderasi beragama dalam interaksi sehari-hari di lingkungan sekolah dan dalam hubungan dengan masyarakat sekitar. Kontribusi: Penelitian ini memberikan kontribusi pada literatur keilmuan, khususnya dalam bidang pendidikan agama Islam dan studi tentang moderasi beragama.